Policies for an Ageing Society Recent Measures and Areas for Further Reform - Casey, Bernard (OECD Economics Department Working Papers, 2003)
This paper provides a synthesis of age-related developments and policies for a range of OECD countries, drawing on recent OECD work. It describes the expected impact of ageing on expenditure and fiscal pressures taking into account the current configuration of age-related policies. Since later retirement appears to be a key policy to easing the burden of ageing, it looks at indicators of the incentives for early retirement via pension systems and other transfer programmes permitting early withdrawal from the labour market for those approaching retirement. The report discussed the different types of age-related reforms undertaken up to now and areas where further reforms appear needed ...